A role for human homologous recombination factors in suppressing microhomology-mediated end joining - Ahrabi, Sara; Sarkar, Sovan; Pfister, Sophia X.; Pirovano, Giacomo; Higgins, Geoff S.; Porter, Andrew C.G.; Humphrey, Timothy C. (Nucleic acids research, 2016)
DNA double-strand breaks (DSBs) are toxic lesions, which if improperly repaired can result in cell death or genomic instability. DSB repair is usually facilitated by the classical non-homologous end joining (C-NHEJ), or homologous recombination (HR) pathways. However, a mutagenic alternative NHEJ pathway, microhomology-mediated end joining (MMEJ), can also be deployed. While MMEJ is suppressed by C-NHEJ, the relationship between HR and MMEJ is less clear. Here, we describe a role for HR genes in suppressing MMEJ in human cells. By monitoring DSB mis-repair using a sensitive HPRT assay, we found that depletion of HR proteins, including BRCA2, BRCA1 or RPA, resulted in a distinct mutational signature associated with significant increases in break-induced mutation frequencies, deletion lengths and the annealing of short regions of microhomology (2-6 bp) across the break-site. This signature was dependent on CtIP, MRE11, POLQ and PARP, and thus indicative of MMEJ. In contrast to CtIP or MRE11, depletion of BRCA1 resulted in increased partial resection and MMEJ, thus revealing a functional distinction between these early acting HR factors. Together these findings indicate that HR factors suppress mutagenic MMEJ following DSB resection.